Mengkaji Pengaruh Aspek Kondisi Sosial Dan Ekonomi Terhadap Minat Anak Keluarga Nelayan Untuk Melanjutkan Pendidikan Ke Perguruan Tinggi - Shendy Andrie Wijaya , Roro Aditya Novi Wardhani (Universitas PGRI Madiun, 2018)
One of the problems on the progress of educational level that is still a lot of basic education age children can no longer go on to secondary school level let alone up to the college level. Many factors affect the condition. The main factors that the ordinary is the reason the family is expensive tuition fees for middle school to College, so that parents are more likely to send his son to elementary education only. Most parents sent his son worked after graduating from SD and SMP, whether it be labor or help parents traveling etc. This happens on the fishing communities in the village a reality Puger Kulon, still many fishermen did not continue her studies up to College. This research is explanatory research classified as research i.e. research to examine relationships between variables that influence or hypothesized. A form of statistical analysis used was Multiple Linear Regression Models. The results of this research show that there are partial and simultaneous influence aspects of social and economic conditions against the interest of the child the family fishermen to continue their education into college. This is shown by the value standard of sig 0,00 < 0,05. The conclusion from this study is there is influence aspects of social and economic conditions against the interest of the child the family fishermen to continue their education into College in district Puger Puger Jember Regency of Kulon Village.